Perception on physical dilapidation building toward the safety of residents and nearby community: Case study Waller Court, Ipoh, Perak / Wan Ezmira Farhanah Khairul Fuad and Muhamad Hilmi Mohamad @ Masri - Khairul Fuad, Wan Ezmira Farhanah; Mohamad @ Masri, Muhamad Hilmi (2023)
The government has suggested and executed affordable housing initiatives since independence. A house that is affordable is one that can provide the fundamental needs of a citizen. However, low-cost housing is frequently plagued by maintenance issues and ineffective management. Building neglect and dilapidated is a severe issue that must be addressed, as it is a long-term issue that affects both the government and the community. Dilapidated buildings that are no longer maintained by the responsible parties have the potential to endanger the safety of residents and those around them. The aim of this research is to identify the perception on physical dilapidation building toward the safety of residents and nearby community in Waller Court. Quantitative approach is used and the findings are the residents' safety has been compromised due to the building's physical dilapidation, although this differs from the nearby community, which is less affected in terms of safety. For future studies, it is suggested that researchers explore the way dilapidated affects issues other than safety and the researcher might utilise this study as a point of reference in the future in performing more in-depth research on the dilapidated of different building types, such as shophouses, pre-war structures, and so on.